The origins and development of high ability - Bock, Gregory; Ackrill, Kate (John Wiley and Sons, 1993)
The Origins and Development of High Ability Chairman: Richard Atkinson 1993 The outstandingly high abilities shown by certain individuals are a valuable human resource. Despite much talk of maximizing human potential, there have been few systematic efforts to increase the number of people capable of exceptional accomplishments, and many questions have yet to be answered fully. How does high ability arise, and how and why does it develop? How can early talents best be identified, and what conditions are most likely to facilitate the development of exceptional children into high-achieving adults? Are a child’s commitment to improving his or her abilities and the encouragement of this by parents and teachers the cause or the result of the child’s talents? Must one be a highly able child to become a highly able adult? Can any motivated, ‘ordinary’ individual who makes sufficient efforts at improvement reach heights of ability normally regarded as indicative of inherent exceptionality, or is a certain genetic constitution a prerequisite? In this book, psychologists and educational specialists address these and other questions from a variety of perspectives. They discuss the extent to which ‘giftedness’ depends on general intelligence, and what factors contribute to an individual being labelled as gifted. The ‘nature versus nurture’ debate is a major theme throughout, with a chapter describing the latest research attempting to identify specific genes that contribute to intelligence. The role an individual’s environment plays in the expression and achievement of high ability is also considered, with parental influences featuring strongly. An examination of the early lives of child prodigies and a study of some mould-breaking creative adults lead to an exploration of the relationship between early giftedness and later achievement. Specialities investigated in particular include mathematics, science, language, music and invention. Recent Ciba Foundation Symposia: No. 174 Experimental and theoretical studies of consciousness Chairman: T. Nagel 1993 ISBN 0 471 93866 1 No. 173 Chronic fatigue syndrome Chairmen: A. Kleinman and S. E. Straus 1993 ISBN 0 471 93618 9
Ciba Foundation symposium ; 178
Keywords: nadané dítě; Child, Gifted; vývoj dítěte; Family Characteristics; Personality Development; psychologie, klinická psychologie; Child Development; charakteristiky rodiny; rozvoj osobnosti